Effectiveness of Patient Education in Improving Knowledge and Wound-Care Adherence in Diabetic Gangrene and Diabetic Foot Disease: A Systematic Review - Prakosa, I Made Andika; Irma Seliana; Sari, Dinda Ayu Permata (Jurnal Kesehatan dan Kedokteran, 2026)
Abstract: Diabetes-related foot wounds can deteriorate into infection and diabetic gangrene, increasing amputation risk when self-care and timely management are inadequate. Objective: This systematic review evaluated the effectiveness of patient education in improving knowledge and wound-care adherence among individuals with diabetic gangrene and related diabetic foot conditions and identified delivery features most likely to support sustained self-care. Methodology: A systematic literature review was conducted across PubMed, CINAHL, Scopus, and Google Scholar (2015–2025) using PRISMA-consistent screening. Eligible evidence included primary quantitative/qualitative studies, systematic reviews, and clinical guidelines addressing patient education/health promotion with knowledge and/or adherence outcomes. Primary studies were appraised using the JBI critical appraisal checklist. Findings: Patient education was consistently associated with improved diabetic foot-care knowledge and, in several studies, better wound-care adherence. Interactive and audiovisual approaches (e.g., video, counseling with demonstration) tended to outperform passive print materials. Sustained adherence was more strongly supported when education was reinforced through mHealth/reminders and when family/caregiver involvement addressed motivational and practical barriers. Implications: Diabetic wound-care programs should emphasize structured, skills-based and audiovisual education, reinforced through follow-up or digital supports, and integrate family-centered components to improve long-term adherence and reduce progression to severe complications. Originality: This review clarifies which educational features modality, reinforcement, and social support are most plausibly linked to sustained adherence, providing a practical framework for designing scalable education strategies for diabetic foot disease, including diabetic gangrene.